Father Abraham Lincoln's relentless struggle to end slavery - Striner, Richard, 1950- (Oxford ; New York : Oxford University Press, 2006)
"Father Abraham challenges recent portraits of Lincoln as an essentially passive politician and reluctant abolitionist. Exhaustively researched and crisply argued, this superb book gives us a new appreciation of Lincoln as moral leader."--BOOK JACKET.
Includes bibliographical references (p. 293-295) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Views on slavery; Lincoln, Abraham, -- 1809-1865 -- Relations with African Americans; Slaves -- Emancipation -- United States; Electronic books